Combination of gradual and rapid weight loss: Effects on physical performances and psychological state in elite judo athletes - Koral, J.; Dosseville, F. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Most athletes participating in fighting sports with specific weight categories as wrestling and judo can compete in a class until 10% below their usual weight. Some studies showed that the weight loss resulting of rapid (e.g. in 3 or 4 days) or a more gradual procedure (e.g. in 3 or 4 weeks) influences physical, cognitive performances and athletes psychological state. In fact, most of elite judo athletes combine a gradual procedure from 2 to 4 weeks and a rapid weight loss a few days just before competition. The aim of this study was to investigate the effects of such weight loss procedure (combination of gradual and rapid weight loss) on physical performance and psychological state in elite judo athletes. Methods Elite judo competitors (n=20) participated in two tests sessions (T1 : 4 weeks before national championship [NC] and T2 : 1 day before NC). Subjects constituted two experimental groups. The first group called diet (n=10) was made up judo competitors with a weight loss between 2 and 6% of their body weight. The second group called control (n=10) had no weight loss (less 2%). At each test session, we measured the weight and estimated the percentage of body fat (BF) from four measurements of skinfold thickness. Moreover, the subjects took part in a serie of physical tests including: (1) vertical jumps (squat-jump [SJ] and counter movement jump [CMJ]), (2) repetitions of judo movements on 5s and 30s (tokui waza 5s [TW-5] and tokui waza 30s [TW-30]) and (3) 10 pull-up with additional load (70 % of 1MR) in which time of the set was measured to calculate the developed mean power (MP). The order of the tests was always similar. The Profile of the Mood States (POMS) was used to assess changes in tension, anger, confusion, vigour, depression and fatigue Results Diet group shows a significant decrease of weight of 4.2% versus 0.3% in control group (p.0.05) and of percentage of BF (p.0.05). No significant differences are shown in SJ (p>0.05) and CMJ (p>0.05) between T1 and T2 in both groups. Performances in TW-5 are not significantly different between T1 and T2 in both groups (p>0.05). A significant difference is shown in TW-30 (p.0.05) due to a significant decrease in T2 in diet group. In MP, a significant increase is observed in control group from T1 and T2 (p.0.05). Psychological scores expressed as a mean and standard deviation are shown in figure 1. The Diet-group and the control-group are not significantly different in T1 (p>0.05). In the control-group, the mood states of confusion, anger, fatigue and tension are higher and the score in vigour decreases in T2, but no significant difference is observed. In the Diet-group, these variations are significant. Discussion/Conclusion The data indicate that a combination of gradual and rapid weight loss adversely affects physical performances and psychological state of elite judo athletes. These findings confirm previous studies on weight loss effects in fighting sports. Consequently, thus question us of the interest to use such methods rather than to remain a constant weight over the whole sporting season